The Development of an African Horse Sickness Virus VP7 Quasi-Crystal Vaccine Candidate in N. benthamiana - Fearon, Shelley Helen (Department of Molecular and Cell Biology, 2020)
African horse sickness (AHS) is a debilitating viral disease affecting equines and has resulted in many disastrous epizootics. To date, no successful therapeutic treatment exists for AHS and the commercially used live-attenuated vaccines (LAVs) have various side effects. Insoluble particulates have been shown to increase immunogenicity when compared to soluble subunit vaccines and previous studies demonstrated protection of BALB/c mice immunised with African horse sickness virus (AHSV) VP7 against a lethal challenge of AHSV-7 (Bailey 2016; Rutkowska et al. 2011; St Clair et al. 1999; Storni et al. 2005; Wade-Evans et al. 1997). This study investigates a safer monovalent vaccine alternative based on plant-produced quasicrystals of the serogroup-specific AHSV structural protein, VP7. AHSV serotype 5 (AHSV-5) VP7 was expressed in Nicotiana benthamiana by means of Agrobacterium-mediated infiltration of plant expression vector pRIC3.0 encoding VP7 and quasi-crystals purified by means of density gradient ultracentrifugation. The presence of AHSV VP7 quasi-crystals was confirmed by western immunoblotting with anti-AHSV VLP guinea-pig serum and characterized using transmission electron microscopy. After optimizing the purification protocol and achieving satisfactory concentrations, AHSV-5 VP7 quasi-crystals were used in guinea-pig immunogenicity studies where the experimental group (n=5) was inoculated with prime- and boostinoculations of between 10 and 50 µg of purified AHSV VP7 quasi-crystals, and the control group (n=5) inoculated with a control inoculum prepared in the identical manner as the vaccine but using a pRIC3.0 expression vector lacking VP7. Western immunoblot analysis of the humoral response showed stimulation of very high titres of anti-VP7 antibodies 28 days after the boost-inoculation. In addition, RNA-seq transcriptome profiling of guinea-pig spleen derived RNA was used to investigate the global immune response to AHSV-5 VP7 quasi-crystals. Thirty genes involved in innate and adaptive immunity were found to be significantly differentially expressed (q≤0.05) in experimental transcriptome data when compared to the control. Differential expression of genes involved in T-helper (Th)1, Th2 and Th17 cell differentiation and the T-cell receptor signalling pathway suggest a possible cell-mediated immune response to AHSV-5 VP7 quasi-crystals. Upregulation of several important cytokines and cytokine receptors were noted in response to VP7 quasi-crystals e.g. TNFSF14, CX3CR1, IFNLR1 and IL17RA. TNFSF14 and CX3CR1 play a role in T-cell proliferation and cytotoxic T-cell responses respectively. And IFNLR1 and IL17RA are key cytokines in antiviral defences. Upregulation of IL17RA suggests a Th17 response which has been reported as a key component in AHSV immunity. To the best of our knowledge, this study is the first to report the expression of plantproduced AHSV VP7 quasi-crystals and the first time that the cell-mediated immune response to these particles has been assessed. While further investigation is needed, these results suggest that AHSV-5 VP7 quasi-crystals produced in N. benthamiana are immunogenic, inducing both humoral and cell-mediated responses.